2013
DOI: 10.1093/jac/dkt284
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypically occult multidrug-resistant Mycobacterium tuberculosis: dilemmas in diagnosis and treatment

Abstract: While MTB RIF G(R) P(S) strains remain relatively uncommon, they can be associated with low-level rifampicin resistance and poorer treatment outcomes with rifampicin-based regimens. This recently recognized form of multidrug-resistant TB should be adequately detected and managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 21 publications
7
43
4
Order By: Relevance
“…This is consistent with two other studies reporting 4 of 94 (4.3%) and 4 of 202 (2.0%) strains with at least one rpoB mutation within the RRDR (7) (8). Two of the four strains had the mutation L533P.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with two other studies reporting 4 of 94 (4.3%) and 4 of 202 (2.0%) strains with at least one rpoB mutation within the RRDR (7) (8). Two of the four strains had the mutation L533P.…”
supporting
confidence: 92%
“…Poor treatment outcome for four of four patients with phenotypically INH-resistant but RMP-susceptible isolates has been described by Williamson et al (7). With similar isolates, Ho et al found one TB relapse case among four patients (8). Recently, among selected first-failure and relapse patients, equally poor first-line retreatment outcomes were reported for strains with common or disputed mutations (21).…”
mentioning
confidence: 84%
“…The clinical relevance of these mutations still needs to be determined, however. Recent retrospective analyses of treatment outcomes in patients with isolates containing low-MIC mutations, such as the 516GAC¡TAC and 526CAC¡AAC mutations, appear to suggest that these mutations might still be associated with poor treatment outcomes in standard RIF-based first-line treatment regimens (32,34,35), but these studies had many unmeasured confounding factors that might have affected the results. In the long term, it will be critical to address the discordant phenotypic standards by which isolates with low-level MIC resistance are evaluated and to conduct studies on the clinical relevance of these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of these lower critical concentrations have come from clinical studies [209][210][211][212][213] and several investigations [214][215][216][217][218][219][220][221] of drug resistance-associated mutations in isolates with MICs below the standard breakpoint. Clinical studies using assumption-free methods such as machine learning have confirmed that these values (table 3) are in fact the MICs above which tuberculosis patients fail combination therapy.…”
Section: Rv1910cmentioning
confidence: 91%
“…Additionally, studies have been done in which treatment failed in patients who were infected with M tuberculosis who had drug target site mutations, but MICs were lower than current breakpoints, and were more consistent with the newly proposed breakpoints. [214][215][216][217][218][219][220][221] Therefore, the proposed concentrations have higher sensitivity for clinical decision making, and should be used to estimate the global burden of MDR tuberculosis.…”
Section: Rv1910cmentioning
confidence: 99%